Analisis Nilai Pendidikan Karakter dalam Web Series Mulih Episode 1 - Uhwah Hasanah; Zuhra Meiliza; St Harpiani (Program Pascasarjana UNU Surakarta, 2023)
This study aims to describe the values of character education in the web series Mulih episode 1. This research is a type of qualitative research. Data collection was carried out using the library and note-taking method. The researcher watched the web series Mulih episode 1 carefully, then recorded the data obtained for processing. Data analysis techniques were carried out by sorting messages in the form of sentences and dialogues that contain character education values in the Mulih web series episode 1. Based on the results of the research, the character education values contained in the Mulih web series episode 1 include: 1) Religious values, in scenes Revelation says hello. 2) The value of appreciating achievement, in the scene Pak Firman congratulates Wahyu. 3) Friendly or communitarian values, in the scene where Wahyu and Parno meet, also at Aiko and Parno's meeting. 4) Honest values, in the scene Wahyu expresses his wishes. 5) The value of curiosity, in the scene Pak Firman asks the reason for Wahyu. 6) The value of social care, in the scene where Parno tries to stop Wahyu from leaving.